Two Small Peptides from Buthus martensii Hydrolysates Exhibit Antitumor Activity Through Inhibition of TNF-α-Mediated Signal Transduction Pathways - Mengshuang Zhu; Shanshan Zhang; Jiyang Tang; Hairong Hou; Lizhen Wang; Houwen Lin; Xuanming Zhang; Meng Jin (Life)
The scorpion Buthus martensii Karsch is edible and has been an essential resource in traditional Chinese medicine for treating numerous diseases. In this study, two small peptides from B. martensii hydrolysates were examined to elucidate their potential against gastric cancer. The small peptides (AK and GK) were identified using the LC-QTOF-MS-based approach. In silico prediction of therapeutic targets, MGC-803 cells and transgenic zebrafish models, and immunoblotting experiments were used to reveal the molecular mechanism of action of the peptides. The peptides AK and GK competitively bound to the receptor to modulate the TNF/TNFR-signaling cascade and alter the tumor microenvironment. EGFR, TP53, MYC, PTEN, and STAT3 were also identified as major functional targets of the peptides. Mechanistically, AK and GK inactivated the TNF-α/EGFR/STAT3-signaling pathway, decreased c-myc protein expression levels, and upregulated p53 and PTEN expression, thereby preventing TNF-α-induced tumor growth. Our findings indicated that AK and GK played a pivotal role in offsetting the inflammatory stimuli that caused gastric cancer cell invasion and highlighted the use of B. martensii resources as functional products with health benefits.